Tuberous Breast and Poland Syndrome: An Underestimated Association? - Forlini, Valentina; Franchelli, Simonetta; Romanini, Maria Victoria (European Journal of Pediatric Surgery, 2024)
Aim of the Study Both Poland syndrome (PS) and tuberous breast (TB) are anomalies affecting the breast, but they are considered mutually exclusive. Our aim was to determine the possible coexistence of PS and TB and to discuss TB management when associated with PS.Methods Between 2010 and 2023, 51 female adolescent PS patients were studied at our center. Among these, we evaluated those who developed TB after puberty. PS diagnosis was made based on the hypoplasia or absence of pectoralis major muscle detected clinically and confirmed radiologically. Breast anomaly on PS side was classified with Thorax Breast and Nipple (TBN) classification: B1 corresponds to breast hypoplasia, B2 to breast aplasia. TB diagnosis was made with a clinical evaluation after puberty. TB cases were classified according to Grolleau classification.Main Results Among 51 postpubertal PS females, we identified 23 (45%) who developed TB. In 3 cases (13%) TB was bilateral, in 20 (87%) contralateral to PS affected side. Age at time of the first surgical procedure was 16 years. Patients were treated with breast implants, fat grafting, rigotomy, local flaps, or a combination of these. TB treatment was performed simultaneously with PS breast reconstruction when feasible, or after it.Conclusions TB incidence in our series was almost twice than in general population. This is the first study demonstrating and quantifying this association. TB deformity must be considered while defining PS surgical path in adolescents. Fat grafting is the first surgical option to treat both anomalies. A multidisciplinary approach is needed to minimize number of surgeries and maximize cosmetic results.
Keywords: tuberous breast; Poland syndrome; breast malformations; breast hypoplasia; breast aplasia